Biogeographic Insights Into the Late Miocene Diversification of the Giant Deep‐Ocean Amphipod Eurythenes - Carolina E. González; Johanna N. J. Weston; Reinaldo Rivera; Marcelo Oliva; Rubén Escribano; Osvaldo Ulloa (Ecology and Evolution)
ABSTRACT Mechanisms driving the spatial and temporal patterns of species distribution in the Earth's largest habitat, the deep ocean, remain largely enigmatic. The late Miocene to the Pliocene (~23–2.58 Ma) is a period that was marked by significant geological, climatic, and oceanographic changes. This transitional period spurred widespread species diversification, particularly among widely distributed benthic scavengers, such as amphipods. Here, we take step toward understanding the long‐term evolutionary processes of amphipod colonization and diversification in the deep ocean by focusing on the model genus Eurythenes S. I. Smith in Scudder, 1882. These large‐bodied scavengers play key roles in benthic communities. We constructed a time‐calibrated phylogeny using two mitochondrial DNA genes by analyzing publicly available data on 14 species of Eurythenes across a global depth range from 839 to 8081 m. The resulting phylogenetic tree reveals a diverse clade, with a common ancestor originating around 11.81 Ma. A gradual increase in the effective population size of Eurythenes was observed, particularly during the Pliocene (~4 Ma). The net diversification rate remained almost constant, with slight increases between the Miocene and Pliocene (~8–4 Ma), and most new species appeared during the latter period. Additionally, reconstruction of the ancestral area suggested that the common ancestor of Eurythenes had a global distribution. A combination of dispersal and sympatric processes, along with environmental factors, such as changes in ocean temperature and sea level, contributed to the present biogeographic distribution of these species. Our findings highlight the importance of historical events, such as plate tectonics and changes in deep‐water circulation, in driving the rapid speciation of Eurythenes and underscore their essential role in shaping deep‐ocean biodiversity.